The Resilience of Inter-basin Transfers to Severe Droughts With Changing Spatial Characteristics - Murgatroyd, Anna; Hall, Jim W. (Frontiers in Environmental Science, 2020)
Faced with the prospect of climate change and growing demands for water, water resources managers are increasingly examining the potential for inter-basin water transfers to alleviate water shortages. However, water transfers are vulnerable to large-scale spatially coherent droughts which may lead to water shortages in neighbouring river basins at the same time. Under climate change, increasingly severe droughts are also expected to have greater spatial extent. We have integrated climate, hydrological and water resource modelling to explore the resilience of new transfer schemes between two neighbouring water companies in Southern England. An extended historical record of river flows and large ensemble of climate change driven future flows were used to explore the effects of spatial and temporal variability. The analysis examines meteorological, hydrological and water resource drought events and how the spatial characteristics of these droughts may change with different transfer arrangements. Results indicate that all drought types examined are expected to increase in frequency and intensity throughout the 21st century, but a new transfer has the capability to increase the resilience of water supplies. The analysis also highlights the importance of testing new water infrastructure against drought events that are more extreme and have different spatial patterns to those in historical records, demonstrating the value of scenario-based approaches to adaptive water resource planning.